A novel HLA‐A*32 allele, A*32:67 was identified by polymerase chain reaction sequence‐based typing in a Chinese individual. Issue 6 (6th March 2015) - He, Y.‐M.; Wang, W.; Han, Z.‐D.; He, J.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐A*32:67 has a single nucleotide difference at position 286 C>A compared with HLA‐A*32:01:01.